Fill’er Up: Automating Hometown News Releases - Kathleen Davis Phillips; Guangming Xiao (Journal of Applied Communications, 1998)
Everyone wants to see their name in print when a special award or honor is won. And such releases bring praise to the news staff. But preparing these individualized news articles for just one or two papers is time-consuming and detracts from writing other releases that have mass market appeal. Assigning students to write the articles and seek addresses for papers requires a lot of supervision. To address these needs, a form was created on the World Wide Web to generate automatic news stories for award winners. The form allows the recipient of the award to share in the responsibility for accurate dissemination.